T-BET and EOMES Accelerate and Enhance Functional Differentiation of Human Natural Killer Cells - Kiekens, Laura; Van Loocke, Wouter; Taveirne, Sylvie; Wahlen, Sigrid; Persyn, Eva; Van Ammel, Els; De Vos, Zenzi; Matthys, Patrick; Van Nieuwerburgh, Filip; Taghon, Tom; Van Vlierberghe, Pieter; Vandekerckhove, Bart; et al. (Frontiers in Immunology, 2021)
T-bet and Eomes are transcription factors that are known to be important in maturation and function of murine natural killer (NK) cells. Reduced T-BET and EOMES expression results in dysfunctional NK cells and failure to control tumor growth. In contrast to mice, the current knowledge on the role of T-BET and EOMES in human NK cells is rudimentary. Here, we ectopically expressed either T-BET or EOMES in human hematopoietic progenitor cells. Combined transcriptome, chromatin accessibility and protein expression analyses revealed that T-BET or EOMES epigenetically represses hematopoietic stem cell quiescence and non-NK lineage differentiation genes, while activating an NK cell-specific transcriptome and thereby drastically accelerating NK cell differentiation. In this model, the effects of T-BET and EOMES are largely overlapping, yet EOMES shows a superior role in early NK cell maturation and induces faster NK receptor and enhanced CD16 expression. T-BET particularly controls transcription of terminal maturation markers and epigenetically controls strong induction of KIR expression. Finally, NK cells generated upon T-BET or EOMES overexpression display improved functionality, including increased IFN-γ production and killing, and especially EOMES overexpression NK cells have enhanced antibody-dependent cellular cytotoxicity. Our findings reveal novel insights on the regulatory role of T-BET and EOMES in human NK cell maturation and function, which is essential to further understand human NK cell biology and to optimize adoptive NK cell therapies.